Quality of service measurement and evaluation in telecommunications: a case study of Africom (Private) Limited - Ndlovu, Sakhile (Midlands State University, 2017)
This research work studied the behaviour of Africom’s converged network, measured and evaluated the QoS of service of the network with the various traffic streams. Its objective was to identify and measure the different metrics that affect the delivery of QoS in the network. Parameters for measuring QoS were be identified and measured and the overall performance of the network evaluated. The approach that was adopted was guided by the subscriber concerns as well as the technical parameters that support conformance to networking standards. The measurement process made use of three methods to measure and evaluate the service: live tests, customer satisfaction surveys, as well as mobile switching centre statistics and monitoring. A conclusion was drawn on whether the different approaches used complement or work against each other in evaluating the QoS of the network under study.